The Impact Of Market Orientation In Corporate Strategy On The Development Of New Products - Zainul Wasik; Wulan Purnamasari; Lia Febria Lina (Journal of Managerial Sciences and Studies, 2024)
In this research, we suggest that corporate strategy affects market orientation, which in turn affects new product activity both directly and indirectly. Thus, we create a framework that connects companies' focus strategies, customer and competitor orientation, and relative emphasis on cost leadership, product differentiation, and focus strategies to new product creation and activity for introduction. Using this approach, we create a simultaneous equations model that is evaluated using survey data from 175 Indonesia companies in the manufacturing sector, spanning various industries and sizes. The unexpected conclusions are that competitor orientation has a negative direct impact on new product activity and a favorable indirect effect through customer orientation, and that a stronger emphasis on a focus strategy leads to a decreased emphasis on consumer orientation. We talk about how these discoveries affect theory and practice.